Individual typological features of judokas of various weight categories - Levitsky, A. G.; Rudenko, G. V.; Tkachuk, M. G.; Kostromin, O. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to conduct a comparative analysis of morphometric indicators among judokas performing in various weight categories.